2020
DOI: 10.3126/bjhs.v4i3.27032
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum uric acid and serum lipid profile in pre- eclampsia- A hospital based case-control study

Abstract: Introduction: Pre-eclampsia, one of the most common medical complication in pregnancy results in considerable maternal and fetal morbidity and mortality. Endothelial dysfunction is a central feature of pre-eclampsia. Elevated serum uric acid level may serve as a marker for early diagnosis of the disease as well as a surrogate for clinical severity of the condition. High serum values of triglycerides, total cholesterol, low- density lipoprotein and and low levels of high density lipoprotein are all significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…About 88.6% of women with PIH have shown that serum TG concentration levels are above the baseline value. This result is in line with the previous study 6,35 . The elevation of serum TG may be due to a decrease in hepatic lipase activity responsible for the endogenous biosynthesis of TG and diminished lipoprotein lipase activity that keeps TG in adipocyte tissue 27 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…About 88.6% of women with PIH have shown that serum TG concentration levels are above the baseline value. This result is in line with the previous study 6,35 . The elevation of serum TG may be due to a decrease in hepatic lipase activity responsible for the endogenous biosynthesis of TG and diminished lipoprotein lipase activity that keeps TG in adipocyte tissue 27 .…”
Section: Discussionsupporting
confidence: 93%
“…This result is in line with the previous study. 6,35 The elevation of serum TG may be due to a decrease in hepatic lipase activity responsible for the endogenous biosynthesis of TG and diminished lipoprotein lipase activity that keeps TG in adipocyte tissue. 27 This contributes to an endothelial pathology directly predisposed in uterine vessels or indirectly via generating small size dense LDL-C (sLDL-C) and/or it should be related to hypercoagulability.…”
Section: Discussionmentioning
confidence: 99%
“…A rapid elevation of uric acid during pregnancy can occur from the 1 st trimester and such event is a precursor and predictor of the commencement of gestational hypertension and pre-eclampsia. In fact, the severity of pre-eclampsia is a direct function of the serum level of uric acid (Roberts et al, 2005;Johnson et al, 2011;Manjareeka and Nanda, 2013;Yalamati et al, 2015;Zangana and Hamadamen, 2018;Rizal et al, 2019). Reverting serum uric acid to normal levels lowers elevated blood pressure to a normal state (Park et al, 2009) but a similar study bizarrely proposed that increasing salt intake reduces serum uric acid concentration (Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%